Reactogenicity and immunogenicity of tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis vaccine (Tdap) in pregnant and nonpregnant women. Issue 42 (8th October 2018) - Fortner, Kimberly B.; Swamy, Geeta K.; Broder, Karen R.; Jimenez-Truque, Natalia; Zhu, Yuwei; Moro, Pedro L.; Liang, Jennifer; Walter, Emmanuel B.; Heine, R. Phillips; Moody, M. Anthony; Yoder, Sandra; Edwards, Kathryn M.
Abstract: Objective: Tetanus toxoid, reduced diphtheria toxoid, and acellular pertusiss (Tdap) vaccine is recommended during each pregnancy, regardless of prior receipt. Data on reactogenicity and immunogenicity, particularly after repeated Tdap, are limited. We compared local injection-site and systemic reactions and serologic response following Tdap in (1) pregnant and nonpregnant women and (2) pregnant women by self-reported prior Tdap receipt. Study design: Pregnant women (gestational age 20–34 weeks) and nonpregnant women receiving Tdap were enrolled in this observational study. Injection-site and systemic reactions were assessed for one week post-vaccination. Pertussis toxin, filamentous hemagglutinin, pertactin, fimbriae, tetanus and diphtheria specific IgG antibody titers were determined by standardized enzyme-linked immunosorbent assay at baseline and 28 days post-vaccination. Reactogenicity and serologic responses were compared by pregnancy status, and within pregnant women by self-reported prior Tdap receipt. Results: 374 pregnant and 225 nonpregnant women were vaccinated. Severe local or systemic reactions or "any" fever were uncommon (≤3% for both groups). Moderate/severe injection-site pain was significantly higher in pregnant (17.9%) versus nonpregnant (11.1%) women, but did not prompt a healthcare visit. Proportions of other moderate/severe or any severe reactions were not significantly higher in pregnant compared to nonpregnant women. Moderate/severe (including pain) and severe reactions were not significantly higher in pregnant women receiving repeat versus first-time Tdap. Antibody titers increased from baseline to post-vaccination for all vaccine antigens in pregnant and nonpregnant women; post-vaccination titers against pertussis toxin and filamentous hemagglutinin were significantly higher in nonpregnant versus pregnant women (p < 0.01). Conclusion: Tdap was well-tolerated in pregnant and nonpregnant women. Pregnant women were more likely to report moderate/severe pain at the Tdap injection-site compared with nonpregnant women, but did not necessitate medical visits. Prior Tdap receipt did not increase occurrence of moderate/severe local or systemic reactions in pregnant women. Serologic responses to all vaccine antigens were robust. Clinical Trial Registration@ClinicalTrials.gov. NCT02209623. https://clinicaltrials.gov/ct2/show/NCT02209623 .